2019
DOI: 10.1093/mnrasl/slz151
|View full text |Cite
|
Sign up to set email alerts
|

SDSS J0159 as an outlier in the MBH–σ space: further clues to support a central tidal disruption event?

Abstract: In this Letter, properties of black hole (BH) mass are well checked for the interesting object SDSS J0159, a changing-look AGN and also a host galaxy of a tidal disruption event (TDE). Through spectral absorption features, the stellar velocity dispersion of SDSS J0159 can be well measured as σ ∼ 81 km/s, leading to SDSS J0159 being an apparent outlier in the M BH − σ space, because of the BH mass estimated through the M BH − σ relation about two magnitudes lower than the reported virial BH mass of about 10 8 M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…A similar argument can be made for the TDE PS18kh (Holoien et al 2019). Although it has a larger BH mass (M BH ≈ 10 6.9 M e ) than 1ES 1927+654, its Hα line is also broader (FWHM = 12,000 km s −1 ), such that their dynamical timescales end up being roughly comparable: (Zhang et al 2019), the dynamical timescale of SDSS J015957.64+003310.5 is close to twice that of 1ES 1927+654, or ∼7 yr. This is roughly comparable to the 10 yr timescale over which velocity changes were detected.…”
Section: Comparison With Other Tdessupporting
confidence: 64%
“…A similar argument can be made for the TDE PS18kh (Holoien et al 2019). Although it has a larger BH mass (M BH ≈ 10 6.9 M e ) than 1ES 1927+654, its Hα line is also broader (FWHM = 12,000 km s −1 ), such that their dynamical timescales end up being roughly comparable: (Zhang et al 2019), the dynamical timescale of SDSS J015957.64+003310.5 is close to twice that of 1ES 1927+654, or ∼7 yr. This is roughly comparable to the 10 yr timescale over which velocity changes were detected.…”
Section: Comparison With Other Tdessupporting
confidence: 64%
“…Similar to what we have previously done in Zhang (2014), Zhang & Feng (2016), Zhang et al (2019), and Zhang (2021a, 2021b to describe the stellar lights included in SDSS spectra of BLAGN, we here exploit a power-law component α × λ β applied to describe the AGN continuum emissions and the 39 simple stellar population templates from Bruzual & Charlot (2003), which include a population age from 5 Myr to 12 Gyr, with three solar metallicities (Z = 0.008, 0.05, and 0.02). Then, through the Levenberg-Marquardt least-squares minimization method applied to the SDSS spectra with both narrow and broad emission lines being masked out, host-galaxy Note.…”
Section: Main Procedures Main Results and Main Discussionmentioning
confidence: 99%
“…There are seven model parameters in the elliptical accretion disk model: the inner boundary r 0 and outer boundary r 1 , in the units of R G (Schwarzschild radius), the inclination angle i of disk-like BLRs, the eccentricity e, the orientation angle f 0 of the elliptical rings, the local broadening velocity σ L , and the line emissivity slope q ( f r ∝ r − q ). Meanwhile, we have also applied the very familiar elliptical accretion disk model; see our studies on double-peaked lines in Wang et al (2005), Zhang (2013aZhang ( , 2015, and Zhang et al (2019). More detailed descriptions on the applied elliptical accretion disk model can be found in Eracleous et al (1995), Storchi-Bergmann et al (2003), and Strateva et al (2003, and as such no further discussions on the elliptical accretion disk model are given in this paper.…”
Section: Main Hypotheses For Estimating Upper Limits Of Sizes Ofmentioning
confidence: 99%
“…The method above to measure stellar velocity dispersions through a single stellar template spectrum is not appropriate to determine host-galaxy contributions. More detailed descriptions of the SSP method can be found in Bruzual & Charlot (2003), Kauffmann et al (2003b), Cid Fernandes et al (2005), Cappellari (2017, and in our previous paper, Zhang (2014), Zhang & Feng (2016), Rakshit et al (2017), Zhang et al (2019), Zhang (2021Zhang ( , 2021aZhang ( , 2021b. Here, we do not show further detailed discussions on the SSP method any longer, but a simple description of the SSP method follows.…”
Section: Methods To Measure the Stellar Velocity Dispersionsmentioning
confidence: 99%
“…Woo et al (2015) reported a virial factor relative to the FWHM as the broad-line width, considering narrow-line Seyfert 1 galaxies. Moreover, considering reverberation-mapped broad-line AGNs, there are some improved M BH -σ relations with quite different slopes, from 3.25 to 6.34, for different samples of objects listed and discussed in Bennert et al (2015), Batiste et al (2017), Zhang et al (2019), and Bennert et al (2021), which should lead to different BH masses of Type 2 AGNs with different M BH -σ relations used.…”
Section: Introductionmentioning
confidence: 99%